Art express - Adams, Eileen; Bignell, Rosemary; Bower, Jane; Grahame, Judy; Kitto, Michelle Claire; Mathieson, Kevin (A&C Black Publishers Ltd, 2009)
A new and complete Art and Design scheme for Primary Class Teachers. Everything you need to teach drawing, painting, printing. sculpture, digital media, collage and textiles.